Genome sequence of Bluetongue virus serotype 17 isolated in Brazil in 2014 - Matos, Ana Carolina Diniz; Rosa, Júlio César Câmara; Nomikou, Kyriaki; Guimarães, Lorena Lima Barbosa; Costa, Érica Azevedo; Guedes, Maria Isabel Maldonado Coelho; Driemeier, David; Lobato, Zélia Inês Portela; Mertens, Peter P.C. (American Society for Microbiology, 2016)
The complete genome sequence of Bluetongue virus (BTV) serotype 17 strain 17/BRA/2014/73, isolated from a sheep in Brazil in 2014, is reported here. All segments clustered with western topotype strains and indicated reassortment events with other BTV from the Americas. The strain 17/BRA/2014/73 represents a novel reference strain for BTV-17 from South America.